Human SAMHD1 restricts the xenotransplantation relevant porcine endogenous retrovirus (PERV) in non-dividing cells. (15th February 2019) - Al-Shehabi, Hussein; Fiebig, Uwe; Kutzner, Juliane; Denner, Joachim; Schaller, Torsten; Bannert, Norbert; Hofmann, Henning
Abstract : The release of porcine endogenous retrovirus (PERV) particles from pig cells is a potential risk factor during xenotransplantation by way of productively infecting the human transplant recipient. Potential countermeasures against PERV replication are restriction factors that block retroviral replication. SAMHD1 is a triphosphohydrolase that depletes the cellular pool of dNTPs in non-cycling cells starving retroviral reverse transcription. We investigated the antiviral activity of human SAMHD1 against PERV and found that SAMHD1 potently restricts its reverse transcription in human monocytes, monocyte-derived dendritic cells (MDDC), or macrophages (MDM) and in monocytic THP-1 cells. Degradation of SAMHD1 by SIVmac Vpx or CRISPR/Cas9 knock-out of SAMHD1 allowed for PERV reverse transcription. Addition of deoxynucleosides alleviated the SAMHD1-mediated restriction suggesting that SAMHD1-mediated degradation of dNTPs restricts PERV replication in these human immune cells. In conclusion, our findings highlight SAMHD1 as a potential barrier to PERV transmission from pig transplants to human recipients during xenotransplantation.